Consensus and controversies regarding the treatment of rhabdomyosarcoma. Issue 2 (14th September 2017) - Borinstein, Scott C.; Steppan, Diana; Hayashi, Masanori; Loeb, David M.; Isakoff, Michael S.; Binitie, Odion; Brohl, Andrew S.; Bridge, Julia A.; Stavas, Mark; Shinohara, Eric T.; Meyer, William H.; Reed, Damon R.; et al.
Abstract: Optimal treatment of rhabdomyosarcoma (RMS) requires multidisciplinary approach, incorporating chemotherapy with local control. Although current therapies are built on cooperative group trials, a comprehensive standard of care to guide clinical decision making has been lacking, especially for relapsed patients. Therefore, we assembled a panel of pediatric and adolescent and young adult sarcoma experts to develop treatment guidelines for managing RMS and to identify areas in which further research is needed. We created algorithms incorporating evidence‐based care for patients with RMS, emphasizing the importance of clinical trials and close integration of all specialties involved in the care of these patients.